Closed-loop optimized nanometal sintering method. (November 2020) - Meng, Fanbo; Huang, Jin; Zhao, Pengbing
Highlights: Stable flash sintering of metallic nanoinks. Closed-loop sintering control by fused multi-sensor data. High-quality inkjet-printing of microstrip antennas. Abstract: Intense pulsed-light sintering is suitable for forming conductive patterns as it exhibits high efficiency and processing speed; however, it has problems such as destructive sinter necks and poor forming stability. To overcome these drawbacks, conductive pattern sintering based on noncontact height and temperature sensor feedback is proposed. This method involves using a dual-camera vision system for extracting the surface features of the scanned surface. In addition, a temperature sensor measures the surface temperature distribution of the sample to evaluate the sintering state. The two sets of data are fused using a variable weight method to comprehensively evaluate the sintered state of the conductive patterns and adjust the parameters of the next sintering operation. This system was utilized for printing and sintering microstrip antennas, and their return loss and patterns were determined experimentally and they were found consistent with those obtained using traditional manufacturing methods. Therefore, the sensor feedback of the intense pulsed-light sintering method improves the pass rate and reduces the duration of the production cycle. Moreover, this is an environmentally friendly method because unlike traditional etching processes, it does not generate large amounts of contaminated solutions.